Prolonged lipopolysaccharide‐induced illness elevates glucagon‐like peptide‐1 and suppresses peptide YY: A human‐randomized cross‐over trial. Issue 18 (18th September 2022) - Brodersen, Katrine; Mose, Maike; Ramer Mikkelsen, Ulla; Jørgensen, Jens Otto Lunde; Festersen Nielsen, Michael; Møller, Niels; Wegeberg, Anne‐Marie; Brock, Christina; Hartmann, Bolette; Holst, Jens Juul; Rittig, Nikolaj
Abstract: Severe systemic inflammation is associated with nausea, loss of appetite, and delayed gastric emptying, which increases hospitalization admission length and mortality rate. There is a lack of human controlled studies exploring gastric emptying rates and underlying mechanisms during inflammatory conditions. We aimed to investigate if systemic inflammation in young men delays gastro‐intestinal transit times, lowers motility, and affects gastrointestinal hormone secretion. This substudy of a randomized crossover trial investigated eight healthy young men on two separate occasions; (I) following an overnight fast (healthy conditions/HC) and (II) fasting and bedrest combined with two lipopolysaccharide (LPS) injections of 1 ng kg −1 following an overnight fast and 0.5 ng kg −1 following another 24 h (systemic inflammation/SI). A standardized protein beverage and a SmartPill capsule (a wireless gastrointestinal monitoring system) were swallowed during each occasion. Whole gut transit time was comparable between HC and SI. SI decreased gastric mean pressure peak amplitude ( p = 0.04) and increased pH rise across the pylorus and small bowel pH ( p = 0.02) compared with HC. Glucagon‐like peptide‐1 was elevated during SI compared with HC ( p = 0.04). Peptide YY was lower during SI compared with HC ( p = 0.007). Prolonged LPS exposure combined with fasting and bedrest elevated glucagon‐like peptide 1 concentrations, which may play a role for the nausea and loss of appetite typically associated with SI. Abstract : Inflammatory conditions prolong gastrointestinal transit times, but randomized humane studies are lacking. During standardized inflammation motility was decreased, glucagon‐like peptide‐1 was elevated and peptide YY lowered. In conclusion, gastrointestinal hormones may take part in the nausea and malnutrition associated with prolonged systemic inflammation.